2023
DOI: 10.1111/sifp.12236
|View full text |Cite
|
Sign up to set email alerts
|

A Girl and a Boy, Are a Bundle of Joy: A Rise in Gender‐Equitable Fertility Preferences in India

Abstract: Within the last decade, declining son preference in Asia has given rise to gender‐equitable fertility preferences. These include daughter preference, gender indifference, and gender balance. Using five rounds of the India National Family Health Surveys, I investigate the sources of the trends in shifting parental preferences for the gender of their children. Over more than a quarter‐century period (1992–1993 to 2019–2021), I find a significant decline in son preference from 40 to 18 percent and an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(215 reference statements)
0
1
0
Order By: Relevance
“…In fact, another study from Bangladesh and India found that having daughters improved mother’s decision-making power and freedom of mobility compared to having sons [ 53 ]. Between 1990 and 2021, son preference in India declined from 40% to 18% likely due to increase in female education and exposure to television that have been associated with greater gender-equitable attitudes [ 54 ]. Furthermore, another recent study from Bangladesh also noted a greater desire for gender balance between children due to increased female education, female employment, and decline in joint family living situations [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another study from Bangladesh and India found that having daughters improved mother’s decision-making power and freedom of mobility compared to having sons [ 53 ]. Between 1990 and 2021, son preference in India declined from 40% to 18% likely due to increase in female education and exposure to television that have been associated with greater gender-equitable attitudes [ 54 ]. Furthermore, another recent study from Bangladesh also noted a greater desire for gender balance between children due to increased female education, female employment, and decline in joint family living situations [ 55 ].…”
Section: Discussionmentioning
confidence: 99%